Effective safety management ethics for construction industry - Zuliza Amina , Zulkifli (2012)
This thesis presents an effective safety management ethics for construction industry in Malaysia. Concerning construction safety performance, based on records of accident and injury rates are high, construction industry regarded as dangerous field of employment. The main objectives of this study are to justify behaviour of unethical self attitude and factors affecting safety performance in construction industry and to propose an effective safety management ethics for construction industry as illustrated in safety poster to overcome the occupational safety and health problems. Focusing on promote effective safety management ethics by safety poster which aimed to remind awareness of construction parties involved in construction to build their safety attitude and personal safety awareness. This study was conducted by survey questionnaire method using survey monkey internet tools to 44 collected respondent's emails consist of personnel that involved in construction industry of safety background or Civil Engineering background. Comparative literature conducted from the resources of government publication, safety books and guidelines also articles and journals that related to safety management ethics of construction industry. From the respondent's survey, I personal factor is the major factor affecting safety performance with the human attitude and behaviour of disobey safety rules and regulations. The comparative literature resulted of proposed five elements of effective safety management ethics to build safety attitude which is site safety environment and culture practice, safety training, procedural and method of works guidelines, machineries and equipments inspection and last but least safety facilities and PPE. Safety attitude evaluation by Based Behaviour System (BBS) and aimed in driving zero harm and zero defect in developing and sustaining safety construction culture in Malaysia.